Pelaksanaan Stimulasi Kecerdasan Linguistik Anak Usia 5-6 Tahun Di Taman Kanak-Kanak Elia Dedikasi Edukasi Kualiva (DEK) Kota Padang - Elsi Safitri (Universitas Negeri Malang, 2022)
This study aims to see how the implementation is to describe the planning, implementation and evaluation of activities carried out by teachers in developing linguistic intelligence for children aged 5-6 years at Elia Kindergarten DEK Padang City. This type of research is descriptive research using a qualitative approach. The subjects of the research were the children of Mickey 2 Kindergarten Elijah DEK Padang City. The informant of this research is the teacher of Mickey 2 Kindergarten Elia DEK Padang City. Data collection techniques used in the form of observation, interviews and documentation. Data analysis techniques are data collection, data reduction, and drawing conclusions. While the validity of the data used is a triangulation technique.The results of this study indicate that the implementation of Stimulation of Linguistic Intelligence for Children aged 5-6 Years at Elia Kindergarten DEK Padang City has been maximized. It can be concluded that the planning, implementation, and evaluation carried out by the teacher can stimulate children's linguistic intelligence as seen by reading aloud and tahfidz activities that can explore children's self and make it easier for teachers to stimulate speaking or language skills in children for children's linguistic intelligence.Keywords: Stimulation; Linguistic Intelligence; Early childhood